(untitled) - Martin, Lawrence L (Boston, 2001)
Includes bibliographical references and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Fund raising; Human services -- Finance; Social service -- Finance; Social work administration; Quản trị công tác xã hội; Dịch vụ con người -- Tài chính